Ethnomathematics: Utilization and Introduction of Geometry Buildings Using Janur (Coconut Leaf) - Dwina Rahayu Saputri; Siti Salamah Br Ginting (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
One area of mathematics that requires a good understanding and depiction of abstract concepts is geometry. Therefore it is necessary to apply realistic learning. One type of realistic learning is ethnomathematics. Ethnomathematics is a bridge between mathematics and culture by linking culture and students' everyday experiences. Traditional crafts that can be lifted are creations from coconut leaves (janur) which can be formed into various kinds of craft creations that contain geometric shapes. The type of research used in this research is descriptive qualitative research. Data collection was used through literature and interviews. The results of the research show that creations from coconut leaves (janur) can be geometric shapes that can be used as ethnomathematics objects. These forms include (1) coins that can be made into hexagons, (2) kerises that have elements of equilateral triangles, right triangles, and parallelograms, (3) diamond bricks that have elements of square geometry lengths and blocks, (4) balls (balans) which have square and cube geometry elements, (5) sinta diamonds which have rhombus geometry elements and rhombus upright prisms. Other geometric elements contained in the janur creations are congruence, angles, and symmetry. Keywords: ethnomathematics, geometry, coconut leaves.